Numerical simulation of ground thermal response in Canadian seasonal frost regions to climate warming - Mohammed Yassir Marrah; Mamadou Fall; Husham Almansour (International Journal of Geo-Engineering, 2023)
Abstract To ensure that public infrastructure can safely provide essential services and support economic activities in seasonal frost regions, the design of their foundation systems must be updated and/or adapted to the impacts of climate change. This objective can only be achieved, if the impact of global warming on the soil thermal behaviour in Canadian seasonal frost regions is well-known and can be predicted. In the present paper, the results of a modeling study to assess and predict the effect of global warming on the thermal regimes of grounds in three Canadian seasonal frost regions (Ottawa, Sudbury, Toronto) are presented and discussed. The results show that future climate changes will significantly affect the soil thermal regimes in seasonal frost Canadian areas. The simulation results indicated a gradual loss in the frost penetration depth due to the climate change, in the three representative sites. The frost period duration will be shorter due to climate change in the three selected regions and will completely disappear in Ottawa and Toronto. However, the impact of climate change would not appear clearly in the first 40 years “up to 2060”. The response of the ground to the effect of climate change is a function of the geotechnical characteristics of the ground and the climate conditions. The numerical tool developed and results obtained will be useful for the geotechnical design of climate-adaptive transportation structures in Canadian seasonal frost areas.